Les facteurs d’émergence et de pérennisation du secteur de l’image en mouvement dans les aires métropolitaines de Lille, de Lyon et de Marseille - Bruno Lusso (Territoire en Mouvement)
In France, the creative industries are traditionally concentrated in the Paris region. During the 1980s, public authorities of the Lille, Lyon and Marseille metropolitan areas have been given more economic powers thanks to the decentralization national policies. So, they have decided to launch different policies into the cinema, audiovisual, software and video games industries. But these creative industries are more or less developed on the basis of different regional assets: local TV or newspapers, filming tradition, HEIs, microelectronics or multimedia industries… However, firms that have largely developed since the beginning of the 2000s are still emergent. In order to ensure the sustainability of these industries, the public authorities have decided to develop ambitious sectorial policies, which are characterized by the building of media districts and the creation of crossmedia professional associations. The aim of these policies is to create a clustering dynamics. Nevertheless, networks dynamics is still very fragile and emergent. These industries development requires a support of public authorities in the long term.